![\large\underline{\bf \red{Step \:by\: Step \:Explanation:}}](https://img.qammunity.org/2021/formulas/mathematics/college/dvd478clkhrmpcw3u2najyjb6y983lgsjw.png)
Let us take ,
- First integer be x .
- Second integer be y .
Also let us consider x > y .
According to first Condition :-
⇒ x - y = 1.
⇒ x = y + 1. .............(i)
According to second Condition :-
⇒ x × y = 30 .
⇒ ( y + 1 )y = 30 . [ From (i) ]
⇒ y² + y = 30.
⇒ y² + y - 30 = 0 .
⇒ y² + 6y - 5y -30 = 0.
⇒ y ( y + 6 ) -5 ( y + 6 ) = 0 .
⇒ ( y + 6 ) ( y - 5 ) = 0 .
![\red{\bf \longmapsto y = 5 , (-6)}](https://img.qammunity.org/2021/formulas/mathematics/college/ykjmw7z4gpkujl6wrpfa9cua4t73zzefu4.png)
Here y can sustain both values 5 and minus 6 as y is an integer.
So , x = -6 , 5 .
Hence possible answers are ,
![\boxed{\purple{\bf x = -6 , y = -5 }}](https://img.qammunity.org/2021/formulas/mathematics/college/r6fepdqqqbf28pe8t95vogfgcf8yrre6ji.png)
![\qquad\qquad\qquad \bf Or](https://img.qammunity.org/2021/formulas/mathematics/college/hgexk9f0wewbj1vupo5dh21b415qo0xry5.png)
![\boxed{\purple{\bf x = 6 , y = 5 }}](https://img.qammunity.org/2021/formulas/mathematics/college/wg51tx4sv2qa7ks4wxpuk3hlop9qk62uck.png)
.